Blown films with improved property profiles

By using a blend of C2C3 random copolymer and vinyl plastics, the problems of existing blown films taking into account both the seal starting temperature, optical properties and mechanical properties are solved, and low sealing starting temperature, improved mechanical properties and excellent sterilization characteristics are achieved.

CN115485120BActive Publication Date: 2025-03-14BOREALIS AG
View PDF 22 Cites 0 Cited by

Patent Information

Application Number
CN202180032958.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-05-18
Filing Date
2021-05-14
Publication Date
2025-03-14
Estimated Expiration
2041-05-14

AI Technical Summary

Technical Problem

Existing blown films are difficult to take into account when pursuing low seal starting temperature, good optical properties and improved mechanical properties, especially when the material properties are easily damaged under sterilization conditions.

Method used

Using a blend containing C2C3 random copolymer and vinyl plastic, a low sealing starting temperature, improved mechanical properties and excellent sterilization characteristics are achieved through specific polymer fractions and comonomer designs.

Benefits of technology

The blown film has a low sealing starting temperature, improved tear resistance and impact strength, maintained good optical properties, and maintained the stability of the material under sterilization conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003924685100000071
    Figure BDA0003924685100000071
  • Figure BDA0003924685100000091
    Figure BDA0003924685100000091
  • Figure BDA0003924685100000101
    Figure BDA0003924685100000101
Patent Text Reader

Abstract

Blown films based on blends of C2C3 random copolymers and C2-based plastomers combine low seal initiation temperature (SIT), good optical properties and improved hardness / impact balance and also show excellent sterilization properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to novel blown films based on blends of C2C3 random copolymers and C2-based plastomers, which combine low seal initiation temperature (SIT), good optical properties and an improved stiffness / impact balance and also show excellent sterilization properties. Background Art

[0002] In many areas of technology, polypropylene is increasingly successfully replacing polyethylene, as newer generations of polypropylene often have stronger properties compared to traditional polyethylene materials. The same applies to the field of blown film, where polypropylene has used molecular engineering to overcome previous material deficiencies in blown film production.

[0003] The blown film industry is gaining increasing importance in a variety of applications, such as in industrial packaging, consumer packaging, bags and sacks, laminating films, barrier films, packaging for food or pharmaceutical products, agricultural films, hygiene products and product packaging.

[0004] Polypropylene can be used in areas where sealing properties play an important role, such as in the food packaging industry, especially when a good combination of transparency and mechanical properties is desired.

[0005] Heat sealing is the main method for manufacturing flexible and semi-rigid packaging. An important indicator of good sealing performance is especially low seal initiation temperature (SIT), which is required to support high speed operation of packaging machines. In addition, packaging materials are also expected to have improved impact strength and other mechanical properties, such as high tear strength.

[0006] Furthermore, it is also desirable for the packaging material to have satisfactory optical properties, such as low haze and / or high clarity.

[0007] In some food applications, such as retort bags or some medical applications, sterilization is required.

[0008] The most common sterilization procedures use heat (steam), radiation (beta rays, electrons or gamma rays) or chemicals (usually ethylene oxide). Steam sterilization is usually carried out at a temperature range of about 120 to 130°C. Therefore, the material should have sufficient thermal stability, such as a melting temperature above the usual steam sterilization temperature of about 120 to 130°C.

[0009] Of course, treating the polymer under the sterilization conditions outlined above can compromise its final properties, especially optical properties such as transparency.

[0010] It is desirable that packaging materials have satisfactory optical properties, such as low haze, while having good mechanical and sealing properties. As a result, improvement in one desired property is often achieved at the expense of at least one other property. In order to address the above problems, various attempts have been made.

[0011] EP 3280768 claims a polymer composition comprising (a) 65.0 to 90.0 wt.-% of a propylene copolymer (A) having (1) a melt flow rate MFR2 (230°C) measured according to ISO 1133 in the range of from above 0.8 to 15.0 g / 10 min, (2) a comonomer content in the range of from 2.0 to less than 12.0 mol-%, (3) a melting temperature in the range of from 125 to less than 143°C, (4) a xylene cold soluble fraction (XCS) in the range of from 17.0 to 45.0 wt.-%, and (5) a glass transition temperature (Tg) in the range of from above -10°C to 2°C; and (b) 10.0 to 35.0 wt.-% of an elastomeric modifier (B), wherein the elastomeric modifier (B) is characterized in that (i) the melt flow rate MFR2 (230°C) measured according to ISO 1133 between the propylene copolymer (A) and the elastomeric modifier (B) is less than 1.0 wt.-%. 489:1999 (E) the difference between the refractive indices (RI) measured at 23° C. is less than 0.015, and (ii) the glass transition temperature (Tg) of the elastomer modifier (B) is equal to or lower than −20° C. The composition is converted into a cast film.

[0012] The XCS of the PP base (a) is rather high, which limits the applicability of the composition due both to low stiffness and the risk of migration into the contents.

[0013] EP 18180768 discloses a cast film made of a C2C3 random copolymer composition, comprising (A) 70.0 to 99.9 wt% of a C2C3 random copolymer having (a) an ethylene content in the range of 2.0 to 4.8 wt%; (b) a melt flow rate MFR2 (230°C / 2.16 kg) measured according to ISO 1133 in the range of 4.0 to 12.0 g / 10 min; (c) a melting temperature Tm determined by DSC according to ISO 11357 of 120 to 135°C; (d) a xylene cold soluble (XCS) fraction of less than 10.0 wt%; and (B) 0.0 to 30.0 wt% of an ethylene-α-olefin plastomer having a thermal conductivity of 860 to 900 kg / m 3and an MFR2 (190°C / 2.16kg) measured according to ISO 1133 in the range of 0.5 to 50.0 g / 10 min, and (C) one or more additives selected from the group consisting of slip agents, anti-blocking agents, UV stabilizers, antistatic agents, α-nucleating agents and antioxidants in a total amount of 0.1 to 5.0 wt.%, based on the composition.

[0014] EP 3031849 discloses a polypropylene monolayer cast comprising a blend of: (a) 85.0 to 98.0 wt% of a Ziegler-Natta catalyzed random propylene copolymer, wherein the random propylene copolymer consists of units derived from propylene and ethylene, and (b) 2.0 to 15.0 wt% of an ethylene-based plastomer, the ethylene-based plastomer having a viscosity of 0.915 g / cm 3 A density according to ISO 1183 of or below and an MFR2 according to ISO 1133 (190° C.; 2.16 kg) in the range of 2.0 to 30 g / 10 min, wherein the amounts of a) and b) add up to 100 wt%.

[0015] Due to the catalyst used, this Ziegler-Natta catalyzed random propylene copolymer based composition has a high XCS and low toughness.

[0016] Thus, while several cast films are known in the art, there remains a need to develop blown films that provide an advantageous combination of low seal initiation temperature, optical properties, and mechanical properties such as tensile modulus, impact strength (DDI), and tear resistance. Summary of the invention

[0017] It is therefore an object of the present invention to provide a blown film, in particular a non-oriented blown film, having excellent sealing properties with good optical properties and an improved hardness / impact balance, in particular with a high tensile modulus, high impact strength and high tear resistance.

[0018] The present invention is based on the discovery that the above requirements for heat sealing applications can be achieved by a specific design of the polyolefin composition, i.e. simultaneously having a low seal initiation temperature (SIT), improved mechanical properties, especially impact and tear strength, and excellent sterilization properties.

[0019] Thus, according to a first aspect, the present invention relates to a blown film comprising at least 95.0% by weight of a blend of components (A) and (B), the blend comprising

[0020] (A) 60.0 wt% to 95.0 wt% of a C2C3 random copolymer, the random copolymer consisting of 45.0 wt% to 85.0 wt% of a polymer fraction (A-1), the polymer fraction (A-1) having

[0021] (i) an ethylene content in the range of 1.5 to 5.0 wt.%, and

[0022] (ii) a melt flow rate MFR2 (230°C / 2.16kg) measured according to ISO 1133 in the range of 0.8 to 8.0 g / 10 min, and

[0023] 15.0 wt% to 55.0 wt% of a polymer fraction (A-2), the polymer fraction (A-2) having

[0024] (i) an ethylene content in the range of 4.0 to 10.0 wt.%, and

[0025] (ii) a melt flow rate MFR2 (230°C / 2.16 kg) measured according to ISO 1133 in the range of 0.1 to 3.0 g / 10 min,

[0026] wherein the ethylene content of the polymer fraction (A-2) is higher than the ethylene content of the polymer fraction (A-1), and the melt flow rate MFR2 (230°C / 2.16kg) of the polymer fraction (A-2) is lower than the MFR2 (230°C / 2.16kg) of the polymer fraction (A-1), and wherein the C2C3 random copolymer has

[0027] (a) a total ethylene content in the range of 1.0 to 7.0 wt. %,

[0028] (b) a melt flow rate MFR2 (230°C / 2.16kg) measured according to ISO 1133 in the range of 0.5 to less than 4.0 g / 10 min, and

[0029] (c) a melting temperature Tm, measured by DSC according to ISO 11357, of 110° C. to 140° C., wherein the copolymer is prepared using a single-site catalyst, and

[0030] (B) 5.0 to 40.0 wt. % of an ethylene-based plastomer having

[0031] (i)860kg / m 3 Up to 900kg / m 3 The density according to ISO 1183, and

[0032] (ii) MFR2 (190°C; 2.16 kg) according to ISO 1133 in the range of 0.1 to 50 g / 10 min,

[0033] (iii) a comonomer selected from C4 to C8 α-olefins,

[0034] The blown film has

[0035] a) a dart drop impact strength (DDI) of at least 60 g to more than 1700 g on a 50 μm blown film as measured according to ASTM D1709, Method A, and

[0036] b) Elmendorf Tear Strength determined according to ISO 6383 / 2 measured in the machine direction (MD) in the range of at least 5.0 N / mm to 50.0 N / mm and in the transverse direction (TD) in the range of at least 80.0 N / mm to 300.0 N / mm. DETAILED DESCRIPTION

[0037] Hereinafter, the present invention is defined in more detail.

[0038] The blown film according to the present invention comprises a blend of a C2C3 random copolymer (A) and an ethylene-based plastomer (B).

[0039] About C2C3 Random Copolymer (A)

[0040] Component (A) may be present in an amount of 60.0 to 95.0 wt%, preferably 65.0 to 93.0 wt%, more preferably 70.0 to 92.0 wt%, based on the total weight of the blend.

[0041] The C2C3 random copolymer (A) of the present invention is a random copolymer of propylene and ethylene as a comonomer.

[0042] The C2C3 random copolymer (A) is obtained in the presence of a metallocene catalyst.

[0043] According to the present invention, the C2C3 random copolymer (A) is characterized by a moderate to low ethylene comonomer content.

[0044] Therefore, the C2C3 random copolymer (A) has a total ethylene content in the range of 1.0 to 7.0 wt%, preferably 1.5 to 6.5 wt%, more preferably 2.0 to 6.0 wt% and even more preferably 2.5 to 5.5 wt%.

[0045] The C2C3 random copolymer (A) has a melt flow rate MFR2 (230°C / 2.16kg) measured according to ISO 1133 in the range of 0.5 to less than 4.0 g / 10 min, preferably 0.7 to 3.5 g / min and more preferably 0.9 to 3.0 g / min.

[0046] Furthermore, the C2C3 random copolymer (A) has a melting temperature Tm measured by DSC according to ISO 11357 in the range of 110 to 140°C, preferably 115 to 135°C, more preferably 118 to 132°C.

[0047] Alternatively, the C2C3 random copolymer (A) may be defined by the xylene cold soluble (XCS) content measured at 25° C. according to ISO 16152; 2005. Thus, preferably, the C2C3 random copolymer (A) features a xylene cold soluble (XCS) content in the range of 0.6 to 12.0 wt.-%, preferably in the range of 1.0 to 10.0 wt.-%, more preferably in the range of 1.5 to 8.0 wt.-% and even more preferably in the range of 2.0 to 6.0 wt.-%.

[0048] The C2C3 random copolymer (A) is bimodal with respect to comonomer content and MFR2 and consists of polymer fractions (A-1) and (A-2).

[0049] Therefore, the C2C3 random copolymer (A) comprises

[0050] 45.0 to 85.0% by weight of the polymer fraction (A-1), the polymer fraction (A-1) having

[0051] (i) an ethylene content in the range of 1.5 to 5.0 wt.%, and

[0052] (ii) a melt flow rate MFR2 (230°C / 2.16kg) measured according to ISO 1133 in the range of 0.8 to 8.0 g / 10 min, and

[0053] 15.0 to 55.0% by weight of a polymer fraction (A-2), the polymer fraction (A-2) having

[0054] (i) an ethylene content in the range of 4.0 to 10.0 wt.%, and

[0055] (ii) a melt flow rate MFR2 (230°C / 2.16 kg) measured according to ISO 1133 in the range of 0.1 to 3.0 g / 10 min,

[0056] The ethylene content of the polymer fraction (A-2) is higher than that of the polymer fraction (A-1), while the melt flow rate MFR2 (230°C / 2.16kg) of the polymer fraction (A-2) is lower than that of the polymer fraction (A-1).

[0057] Preferably, the C2C3 random copolymer (A) comprises 50.0 to 80.0 wt% of the polymer fraction (A-1) and 20.0 to 50.0 wt% of the polymer fraction (A-2).

[0058] More preferably, the C2C3 random copolymer (A) comprises 55.0 to 75.0 wt% of the polymer fraction (A-1) and 25.0 to 45.0 wt% of the polymer fraction (A-2).

[0059] Preferably, the polymer fraction (A-1) has an ethylene content in the range of 1.8 to 4.5 wt% and more preferably in the range of 2.0 to 4.0 wt%.

[0060] The melt flow rate MFR2 (230° C. / 2.16 kg) of the polymer fraction (A-1) measured according to ISO 1133 is preferably in the range of 1.0 to 6.5 g / 10 min, more preferably in the range of 2.0 to 5.0 g / 10 min.

[0061] The polymer fraction (A-2) preferably has an ethylene content in the range of 4.5 to 9.0 wt% and more preferably in the range of 4.7 to 8.0 wt%.

[0062] The melt flow rate MFR2 (230°C / 2.16 kg) measured according to ISO 1133 of polymer fraction (A-2) is preferably in the range of 0.2 to 2.5 g / 10 min and more preferably in the range of 0.2 to 2.0 g / 10 min, such as 0.2 to 1.8 g / 10 min.

[0063] The C2C3 random copolymer (A) is thus preferably prepared by polymerizing propylene and ethylene in the presence of a metallocene catalyst by a sequential polymerization process comprising at least two reactors connected in series.

[0064] Thus, the C2C3 random copolymer (A) is prepared in a sequential polymerization process comprising at least two polymerization reactors (R1) and (R2), wherein in the first polymerization reactor (R1) a first polymer fraction (A-1) is produced, which is subsequently transferred to the second polymerization reactor (R2). Then in the second polymerization reactor (R2), a second polymer fraction (A-2) is produced in the presence of the first polymer fraction (A-1).

[0065] The polymerization process suitable for producing the C2C3 random copolymer (A) generally comprises at least two polymerization stages and each stage can be carried out in solution, slurry, fluidized bed, bulk or gas phase.

[0066] The term "polymerization reactor" shall indicate that the main polymerization takes place. Thus, in case the process consists of one or two polymerization reactors, this definition does not exclude the option that the overall system comprises a prepolymerization step, for example in a prepolymerization reactor. The term "consisting of" is a closed description only with respect to the main polymerization reactor.

[0067] The term "sequential polymerization process" means that the C2C3 random copolymer (A) is produced in at least two reactors connected in series. Therefore, such a polymerization system comprises at least a first polymerization reactor (R1) and a second polymerization reactor (R2), and optionally a third polymerization reactor (R3).

[0068] The first polymerization reactor (R1) is preferably a slurry reactor and can be any continuous or simple batch stirred tank reactor or loop reactor operating in bulk or slurry. Bulk refers to polymerization in a reaction medium comprising at least 60% (w / w) monomers. According to the present invention, the slurry reactor is preferably a (bulk) loop reactor.

[0069] The second polymerization reactor (R2) and the optional third polymerization reactor (R3) are preferably gas phase reactors (GPR), i.e. a first gas phase reactor (GPR1) and a second gas phase reactor (GPR2). The gas phase reactor (GPR) according to the present invention is preferably a fluidized bed reactor, a fast fluidized bed reactor or a settled bed reactor or any combination thereof.

[0070] A preferred multi-stage process is a "loop-gas phase" process such as that developed by Borealis (known as Technology) is described, for example, in patent literature, such as EP 0 887 379, WO 92 / 12182, WO 2004 / 000899, WO 2004 / 111095, WO 99 / 24478, WO 99 / 24479 or WO 00 / 68315.

[0071] Another suitable slurry-gas phase process is Basell's Craftsmanship.

[0072] Preferably, in the process of the present invention for producing a C2C3 random copolymer composition as described above, the conditions for the first reactor (R1), i.e. the slurry reactor (SR), such as the loop reactor (LR), of step (a) may be the following conditions:

[0073] The temperature is in the range of 40°C to 110°C, preferably between 60°C and 100°C, more preferably between 65°C and 95°C,

[0074] The pressure is in the range of 20 to 80 bar, preferably between 40 and 70 bar,

[0075] Hydrogen can be added for controlling the molar mass in a manner known per se.

[0076] Subsequently, the reaction mixture of the first reactor (R1) is transferred to the second reactor (R2), i.e. the gas phase reactor (GPR1), wherein the conditions are preferably the following:

[0077] The temperature is in the range of 50°C to 130°C, preferably between 60°C and 100°C,

[0078] The pressure is in the range of 5 bar to 50 bar, preferably between 15 bar and 35 bar,

[0079] Hydrogen can be added for controlling the molar mass in a manner known per se.

[0080] The C2C3 random copolymer (A) according to the present invention is produced in the presence of a metallocene catalyst.

[0081] Therefore, the C2C3 random copolymer (A) is produced by a process comprising the steps of:

[0082] a) polymerizing propylene and ethylene in a first reactor (R1) to obtain a polymer fraction (A-1) of a C2C3 random copolymer (A),

[0083] b) transferring the polymer fraction (A-1) and the unreacted comonomer in the first reactor to a second reactor (R2),

[0084] c) feeding propylene and ethylene to the second reactor (R2),

[0085] d) polymerizing propylene and ethylene in the second reactor (R2) and in the presence of the polymer fraction (A-1) to obtain a polymer fraction (A-2),

[0086] The polymer fraction (A-1) and the polymer fraction (A-2) form a C2C3 random copolymer (A) as described above, wherein the polymerization occurs in the presence of a metallocene catalyst comprising (i) a complex of formula (I):

[0087]

[0088] wherein M is zirconium or hafnium; each X is a sigma ligand;

[0089] L is a divalent bridge selected from -R'2C-, -R'2C-CR'2-, -R'2Si-, -R'2Si-SiR'2-, -R'2Ge-, wherein each R' is independently a hydrogen atom, a C1-C 20 -hydrocarbon, tri(C1-C20 -alkyl)silyl, C6-C 20 -Aryl, C7-C 20 -aralkyl or C7-C 20 - alkylaryl;

[0090] R 2 and R 2 ' are each independently C1-C1 optionally containing one or more heteroatoms from Groups 14 to 16 of the Periodic Table of Elements 20 - a hydrocarbon group;

[0091] R 5 ' is a C containing one or more heteroatoms from Groups 14 to 16 of the Periodic Table of Elements, which is optionally substituted by one or more halogen atoms 1-20 - a hydrocarbon group;

[0092] R 6 and R 6 ' are each independently hydrogen or C optionally containing one or more heteroatoms from Groups 14 to 16 of the Periodic Table of Elements 1-20 -hydrocarbyl group; wherein R 6 'Preferably a tertiary alkyl group;

[0093] R 7 is hydrogen or optionally contains one or more heteroatoms from Groups 14 to 16 of the Periodic Table of Elements 1-20 - a hydrocarbon group, and R 7 ' is hydrogen;

[0094] Ar and Ar' are each independently optionally replaced by one or more R 1 a radical-substituted aryl or heteroaryl group having up to 20 carbon atoms;

[0095] Each R 1 C 1-20 - a hydrocarbon group, or two R on adjacent carbon atoms 1 The group can be taken together with the Ar or Ar' group to form a fused 5 or 6 membered non-aromatic ring which itself is optionally substituted by one or more R 4 Group substitution; each R 4 C 1-20 - a hydrocarbyl group; and

[0096] (ii) A promoter comprising at least one or two compounds of metals of Group 13 of the Periodic Table of Elements, such as Al and / or boron compounds.

[0097] More preferably, a cocatalyst system comprising a boron-containing cocatalyst (such as a borate cocatalyst) and an aluminoxane cocatalyst is used.

[0098] Even more preferably, the catalyst is supported on a silica support.

[0099] About Catalyst:

[0100] Typically, the catalyst system used in the present invention can be prepared as described in WO 2018 / 122134 A1. The catalyst can be used in a supported or unsupported form, preferably in a supported form. The particulate support material used is preferably an organic or inorganic material, such as silica, alumina or zirconium oxide, or a mixed oxide, such as silica-alumina, in particular silica, alumina or silica-alumina. Preferably, a silica support is used. The technician knows the procedures required for supporting the metallocene catalyst.

[0101] Particularly preferably, the support is a porous material so that the complex can be loaded into the pores of the support, for example using methods similar to those described in WO94 / 14856 (Mobil), WO95 / 12622 (Borealis) and WO2006 / 097497.

[0102] The average particle size of the silica support can generally be in the range from 10 to 100 μm. However, it has been shown that particular advantages can be achieved if the support has an average particle size of from 15 to 80 μm, preferably from 18 to 50 μm.

[0103] The silica support may have an average pore size in the range of 10 to 100 nm and a pore volume of 1 to 3 mL / g.

[0104] Examples of suitable support materials are, for example, ES757 produced and sold by PQ, Sylopol 948 produced and sold by Grace or SUNSPERA DM-L-303 silica produced by AGC Si-Tech. Before use in the catalyst preparation, the support can optionally be calcined to achieve an optimum silanol group content.

[0105] The use of these vectors is routine in the art.

[0106] Preferred complexes used in the present invention have formula (II') or (II)

[0107]

[0108] wherein M is zirconium or hafnium;

[0109] Each X is independently a hydrogen atom, a halogen atom, C 1-6 -alkoxy group, C 1-6 - an alkyl, phenyl or benzyl group;

[0110] L is a divalent bridge selected from -R'2C-, -R'2C-CR'2-, -R'2Si-, -R'2Si-SiR'2-, -R'2Ge-, wherein each R' is independently a hydrogen atom, C 1-20 -alkyl, C 3-10 -cycloalkyl, tri(C 1-20 -alkyl)silyl, C 6-20 -Aryl, C 7-20 -aralkyl or C 7-20 - alkylaryl;

[0111] R 2 or R 2' Each of C 1-10 - an alkyl group;

[0112] R 5' C 1-10 -alkyl group or Z'R 3' Group;

[0113] R 6 is hydrogen or C 1-10 - an alkyl group;

[0114] R 6' C 1-10 -alkyl group or C 6-10 - an aryl group; preferably a tertiary alkyl group;

[0115] R 7 For hydrogen, C 1-6 -alkyl group or ZR 3 group, and R 7' is hydrogen;

[0116] Z and Z' are independently O or S;

[0117] R 3' C 1-10 -alkyl group or C optionally substituted by one or more halogen groups 6-10 - aryl groups;

[0118] R 3 C 1-10 - an alkyl group;

[0119] Each n is independently 0 to 4, such as 0, 1 or 2;

[0120] And each R 1 Independently for C 1-20 - Hydrocarbyl groups, such as C 1-10 -alkyl group.

[0121] Further preferred complexes used in the present invention have the formula (III') or (III):

[0122]

[0123] M is zirconium or hafnium;

[0124] Each X is independently a hydrogen atom, a halogen atom, C 1-6 -alkoxy group, C 1-6 - an alkyl, phenyl or benzyl group;

[0125] L is a divalent bridge selected from -R'2C- or -R'2Si-, wherein each R' is independently a hydrogen atom, C 1-20 -alkyl or C 3-10 - cycloalkyl;

[0126] R 6 is hydrogen or C 1-10 - an alkyl group;

[0127] R 6 ' is C 1-10 -alkyl group or C 6-10 - an aryl group, preferably a tertiary alkyl group;

[0128] R 7 For hydrogen, C 1-6 -alkyl or OC 1-6 -alkyl; Z' is O or S;

[0129] R 3 ' is C 1-10 -alkyl group or C optionally substituted by one or more halogen groups 6-10 - aryl groups;

[0130] n is independently 0 to 4, such as 0, 1 or 2; and each R 1 Independently for C 1-10 -alkyl group.

[0131] Further preferred complexes used in the present invention have the formula (IV') or (IV):

[0132]

[0133] M is zirconium or hafnium;

[0134] Each X is independently a hydrogen atom, a halogen atom, C 1-6 -alkoxy group, C 1-6 - an alkyl, phenyl or benzyl group;

[0135] Each R' is independently a hydrogen atom, C 1-20 -alkyl or C 3-7 - cycloalkyl;

[0136] R6 is hydrogen or C 1-10 - an alkyl group;

[0137] R 6 ' is C 1-10 -alkyl group or C 6-10 - an aryl group, preferably a tertiary alkyl group;

[0138] R 7 For hydrogen, C 1-6 -alkyl or OC 1-6 -alkyl; Z' is O or S;

[0139] R 3 ' is C 1-10 -alkyl group or C optionally substituted by one or more halogen groups 6-10 - aryl groups;

[0140] n is independently 0, 1 to 2; and each R 1 Independently for C 3-8 -alkyl group.

[0141] Most preferably, the complex used in the present invention has formula (V') or (V):

[0142]

[0143] Wherein each X is independently a hydrogen atom, a halogen atom, C 1-6 -alkoxy group, C 1-6 - an alkyl, phenyl or benzyl group;

[0144] R' is independently C 1-6 -alkyl or C 3-10 - cycloalkyl;

[0145] R 1 Independently for C 3-8 -alkyl;

[0146] R 6 is hydrogen or C 3-8 - an alkyl group;

[0147] R 6 ' is C 3-8 -alkyl group or C 6-10 -aryl group; preferably tertiary C 4-8 - an alkyl group;

[0148] R 3 ' is C 1-6 -alkyl group or C optionally substituted by one or more halogen groups 6-10 - aryl groups;

[0149] and n is independently 0, 1 or 2.

[0150] Particular compounds of the present invention include:

[0151] Racemic-trans-Me2Si(2-Me-4-Ph-6-tBu-Ind)(2-Me-4-Ph-5-OMe-6-tBu-Ind)ZrCl2,

[0152] Racemic-trans-Me2Si(2-Me-4-(p-tBuPh)-Ind)(2-Me-4-Ph-5-OMe-6-tBu-Ind)ZrCl2

[0153] Racemic-trans-Me2Si(2-Me-4-(3,5-di-tBuPh)-6-tBu-Ind)(2-Me-4-Ph-5-OMe-6-tBu-Ind)ZrCl2

[0154] Racemic-trans-Me2Si(2-Me-4-Ph-6-tBu-Ind)(2-Me-4,6-di-Ph-5-OMe-Ind)ZrCl2

[0155] Racemic-trans-Me2Si(2-Me-4-(p-tBuPh)-Ind)(2-Me-4-Ph-5-OC6F5)-6-iPr-Ind)ZrCl2

[0156] Racemic-trans-Me(CyHex)Si(2-Me-4-Ph-6-tBu-Ind)(2-Me-4-Ph-5-OMe-6-tBu-Ind)ZrCl2

[0157] Racemic-trans-Me2Si(2-Me-4-(3,5-di-tBuPh)-7-Me-Ind)(2-Me-4-Ph-5-OMe-6-tBu-Ind)ZrCl2

[0158] Racemic-trans-Me2Si(2-Me-4-(3,5-di-tBuPh)-7-OMe-Ind)(2-Me-4-Ph-5-OMe-6-tBu-Ind)ZrCl2

[0159] Racemic-trans-Me2Si(2-Me-4-(p-tBuPh)-6-tBu-Ind)(2-Me-4-Ph-5-OMe-6-tBu-Ind)ZrCl2

[0160] Racemic-trans-Me2Si(2-Me-4-(p-tBuPh)-Ind)(2-Me-4-(4-tBuPh)-5-OMe-6-tBu-Ind)ZrCl2

[0161] Racemic-trans-Me2Si(2-Me-4-(p-tBuPh)-Ind)(2-Me-4-(3,5-tBu2Ph)-5-OMe-6-tBu-Ind)ZrCl2

[0162] Racemic-trans-Me2Si(2-Me-4-(p-tBuPh)-Ind)(2-Me-4-Ph-5-OiBu-6-tBu-Ind)ZrCl2

[0163] Most preferably, rac-trans-Me2Si(2-Me-4-(p-tBuPh)-Ind)(2-Me-4-Ph-5-OMe-6-tBu-Ind)ZrCl2 is used.

[0164] The ligands required for forming the complex of the present invention and the catalyst of the present invention can be synthesized by any method, and a skilled organic chemist will be able to come up with various synthesis schemes for making the necessary ligand materials. For example, WO2007 / 116034 discloses the necessary chemical reactions. Synthesis schemes can also be found in WO2002 / 02576, WO2011 / 135004, WO2012 / 084961, WO2012 / 001052, WO2011 / 076780, WO2013 / 007650, WO2015 / 158790 and WO2018 / 122134. The examples section also provides sufficient guidance for the technician.

[0165] Catalyst

[0166] As is known in the art, a cocatalyst is generally required to form an active catalytic species. Cocatalysts for activating metallocene catalysts comprising one or more compounds of Group 13 metals, such as organoaluminum compounds or boron-containing cocatalysts or combinations thereof, are suitable for use in the present invention.

[0167] In a preferred embodiment of the present invention, a cocatalyst system comprising a boron-containing cocatalyst (eg, a borate cocatalyst) and an aluminoxane cocatalyst is used.

[0168] Thus, the single site polymerization catalyst system used in the present invention may comprise (i) the complex as defined above and an aluminoxane cocatalyst.

[0169] The aluminoxane cocatalyst may be one of formula (VI):

[0170]

[0171] wherein n is 6 to 20 and R has the following meanings.

[0172] Aluminoxanes are formed upon partial hydrolysis of organoaluminum compounds, such as compounds having the formula AlR3, AlR2Y and Al2R3Y3, wherein R can be, for example, C1-C 10 -alkyl, preferably C1-C5-alkyl, or C3-C 10 -Cycloalkyl, C7-C 12 -aralkyl or C7-C 12 - alkylaryl and / or phenyl or naphthyl, and wherein Y can be hydrogen, halogen, preferably chlorine or bromine, or C1-C 10 - alkoxy, preferably methoxy or ethoxy. The oxygen-containing aluminoxane obtained is usually not a pure compound but a mixture of oligomers of the formula (VI).

[0173] A preferred aluminoxane is methylaluminoxane (MAO).

[0174] Since the aluminoxanes used as cocatalysts according to the invention are not pure compounds due to the way they are prepared, the molar concentrations of the aluminoxane solutions hereinafter are based on their aluminum content.

[0175] According to the invention, it is also possible to use boron-containing promoters.

[0176] Boron-containing cocatalysts of interest include cocatalysts of formula (VII)

[0177] BY3(VII)

[0178] Wherein Y is the same or different and is a hydrogen atom, an alkyl group having 1 to about 20 carbon atoms, an aryl group having 6 to about 15 carbon atoms, an alkaryl group, an aralkyl group, a haloalkyl group or a haloaryl group, each having 1 to 10 carbon atoms in the alkyl group and 6 to 20 carbon atoms in the aryl group, or fluorine, chlorine, bromine or iodine. Preferred embodiments of Y are fluorine, trifluoromethyl, aromatic fluorinated groups such as p-fluorophenyl, 3,5-difluorophenyl, pentafluorophenyl, 3,4,5-trifluorophenyl and 3,5-bis(trifluoromethyl)phenyl. Preferred options are trifluoroborane, tris(4-fluorophenyl)borane, tris(3,5-difluorophenyl)borane, tris(4-fluoromethylphenyl)borane, tris(2,4,6-trifluorophenyl)borane, tris(pentafluorophenyl)borane, tris(3,5-difluorophenyl)borane and / or tris(3,4,5-trifluorophenyl)borane.

[0179] Tris(pentafluorophenyl)borane is particularly preferred.

[0180] However, preference is given to using borates as boron-containing promoters, ie compounds comprising borate.

[0181] These compounds usually contain anions of the formula:

[0182] (Z)4B-(VIII)

[0183] wherein Z is an optionally substituted phenyl derivative, the substituent being a halo-C 1-6 - an alkyl or halogen group. Preferred options are fluoromethyl or trifluoromethyl. Most preferably, the phenyl group is perfluorinated.

[0184] Such ionic promoters preferably contain a weakly coordinating anion such as tetrakis(pentafluorophenyl)borate or tetrakis(3,5-bis(trifluoromethyl)phenyl)borate. Suitable counterions are protonated amine or aniline derivatives such as methylammonium, aniline, dimethylammonium, diethylammonium, N-methylaniline, diphenylammonium, N,N-dimethylaniline, trimethylammonium, triethylammonium, tri-n-butylammonium, methyldiphenylammonium, pyridinium, p-bromo-N,N-dimethylaniline or p-nitro-N,N-dimethylaniline.

[0185] Preferred ionic compounds that can be used according to the present invention include:

[0186] Tributylammonium tetrakis(pentafluorophenyl)borate,

[0187] Tributylammonium tetrakis(trifluoromethylphenyl)borate,

[0188] Tributylammonium tetrakis(4-fluorophenyl)borate,

[0189] N,N-Dimethylcyclohexylammonium tetrakis(pentafluorophenyl)borate,

[0190] N,N-Dimethylbenzylammonium tetrakis(pentafluorophenyl)borate,

[0191] N,N-Dimethylanilinium tetrakis(pentafluorophenyl)borate,

[0192] N,N-Di(propyl)ammoniumtetrakis(pentafluorophenyl)borate,

[0193] Di(cyclohexyl)ammonium tetrakis(pentafluorophenyl)borate,

[0194] Triphenylcarbonium tetrakis(pentafluorophenyl)borate,

[0195] Or ferrocenium tetrakis(pentafluorophenyl)borate.

[0196] Preferably triphenylcarbonium tetrakis(pentafluorophenyl)borate,

[0197] N,N-Dimethylanilinium tetrakis(pentafluorophenyl)borate,

[0198] N,N-dimethylcyclohexylammonium tetrakis(pentafluorophenyl)borate, or

[0199] N,N-Dimethylbenzylammonium tetrakis(pentafluorophenyl)borate.

[0200] It is particularly preferred according to the present invention to use an aluminoxane cocatalyst such as MAO together with a boron-containing cocatalyst such as a borate cocatalyst.

[0201] Suitable amounts of promoter are well known to those skilled in the art.

[0202] Preferably, the amount of cocatalyst is chosen so as to achieve the molar ratios defined below.

[0203] The molar ratio of boron (B) to the metal ion (M) of the metallocene (preferably zirconium) Boron / M can be in the range of 0.1:1 to 10:1 mol / mol, preferably in the range of 0.3:1 to 7:1, especially in the range of 0.3:1 to 5:1 mol / mol.

[0204] Even more preferably, the molar ratio of the feed amount of boron (B) to the metal ion (M) of the metallocene, preferably zirconium, B / M is from 0.3:1 to 3:1.

[0205] The molar ratio Al / M of Al from aluminoxane to the metal ion (M) of the metallocene (preferably zirconium) may be in the range of 1:1 to 2000:1 mol / mol, preferably in the range of 10:1 to 1000:1, and more preferably in the range of 50:1 to 600:1 mol / mol.

[0206] The C2C3 random copolymer (A) of the present invention may optionally contain one or more additives, the total amount of the additives being 0.1 to 5.0 wt % based on the total weight of the copolymer (A), and the additives are selected from the group consisting of slip agents, anti-blocking agents, UV stabilizers, antistatic agents, α-nucleating agents and antioxidants.

[0207] Such additives are well known to those skilled in the art.

[0208] Typically, these additives are added in amounts of 100 to 1.000 ppm for each individual component.

[0209] Preferably, at least an antioxidant is added.

[0210] About Vinyl Plastomers (B)

[0211] The blend for blown film further comprises component (B), which is a vinyl plastomer.

[0212] Component (B) may be present in an amount of 5.0 to 40.0 wt%, preferably 7.0 to 35.0 wt%, more preferably 8.0 to 30.0 wt%, based on the total weight of the blend.

[0213] Vinyl plastic has a density of 860 to 900 kg / m 3 In the range of 865 to 895 kg / m 3 In the range of 870 to 890 kg / m 3 and even more preferably in the range of 875 to 890 kg / m 3 The density is within the range according to ISO 1183.

[0214] The MFR2 (190°C / 2.16kg) of the ethylene-based plastomer measured according to ISO 1133 is in the range of 0.1 to 50.0 g / 10 min, preferably in the range of 0.3 to 20.0 g / 10 min, more preferably in the range of 0.5 to 10.0 g / 10 min and more preferably in the range of 0.8 to 5.0 g / 10 min.

[0215] Suitable ethylene-based plastomers may have an ethylene content of 60.0 to 95.0 wt %, preferably 65.0 to 90.0 wt % and more preferably 70.0 to 88.0 wt %. The comonomer contribution is preferably at most 40.0 wt %, more preferably at most 35.0 wt %. The comonomer content of conventional ethylene-based plastomers is well known to those skilled in the art.

[0216] Ethylene plastomers are copolymers of ethylene and C4 to C8 alpha-olefins. Suitable C4 to C8 alpha-olefins include 1-butene, 1-hexene and 1-octene, preferably 1-butene or 1-octene and more preferably 1-octene. Preferably, copolymers of ethylene and 1-octene are used.

[0217] The melting point (measured by DSC according to ISO 11357-3:1999) of a suitable vinyl plastomer may be below 130° C., preferably below 120° C., more preferably below 110° C. and most preferably below 100° C. A reasonable lower limit for the melting point of a suitable vinyl plastomer may be 30° C. A typical melting point range is from 33 to 115° C.

[0218] Furthermore, suitable ethylene-based plastomers may have a glass transition temperature Tg (measured by DMTA according to ISO 6721-7) below -40°C, preferably below -54°C, more preferably below -58°C.

[0219] The Mw / Mn value of the ethylene-based plastomer, which represents the breadth of the molecular weight distribution (MWD), is preferably in the range of 1.5 to 5.0, more preferably in the range of 2.0 to 4.5, and even more preferably in the range of 2.5 to 4.0.

[0220] The ethylene-based plastomers may be unimodal or multimodal, preferably unimodal.

[0221] Preferably, the PE elastomer is a metallocene-catalyzed polymer, although Ziegler-Natta based polyethylene elastomers are also possible.

[0222] Suitable ethylene plastomers may be any copolymers of ethylene and C4 to C8 alpha olefins having the above-mentioned properties, which copolymers are especially commercially available under the trade name Queo from Borealis AG (Austria), under the trade name Engage or Affinity from The Dow Chemical Company (USA), or under the trade name Tafmer from Mitsui.

[0223] Alternatively, the vinyl plastomers can be prepared by known processes in a one-stage or two-stage polymerization process, including solution polymerization, slurry polymerization, gas phase polymerization or a combination thereof, in the presence of a suitable catalyst known to those skilled in the art, such as a vanadium oxide catalyst or a single-site catalyst (e.g., a metallocene) or a constrained geometry catalyst.

[0224] Preferably, these vinyl plastomers are prepared by a one-stage or two-stage solution polymerization process, especially by a high temperature solution polymerization process at a temperature above 100°C.

[0225] This type of process is essentially based on the polymerization of monomers and suitable copolymers in a liquid hydrocarbon solvent in which the resulting polymer is soluble. The polymerization is carried out at a temperature above the melting point of the polymer, thus obtaining a polymer solution. This solution is flashed in order to separate the polymer from the unreacted monomers and the solvent. The solvent is then recovered and recycled in the process.

[0226] Preferably, the solution polymerisation process is a high temperature solution polymerisation process, using a polymerisation temperature above 100° C. Preferably, the polymerisation temperature is at least 110° C., more preferably at least 150° C. The polymerisation temperature may be as high as 250° C.

[0227] In such a solution polymerization process, preferably the pressure is in the range of 10 to 100 bar, preferably 15 to 100 bar and more preferably 20 to 100 bar.

[0228] The liquid hydrocarbon solvent used is preferably C 5-12 - hydrocarbons, which may be unsubstituted or replaced by C 1-4Alkyl substituted, such as pentane, methylpentane, hexane, heptane, octane, cyclohexane, methylcyclohexane and hydrogenated naphtha. More preferably, unsubstituted C 6-10 - Hydrocarbon solvents.

[0229] A known solution technology suitable for the process according to the invention is the Borceed technology.

[0230] It will be appreciated that the vinyl plastomers may contain standard polymer additives.

[0231] Blown Film

[0232] The present invention relates to blown films comprising at least 95.0 wt. %, more preferably at least 98.0 wt. % and even more preferably at least 99.0 wt. % of the blend of components (A) and (B) described above.

[0233] Furthermore, the blown film of the present invention preferably consists of the blend as the only polymer component. However, it is to be understood herein that the film may contain other components such as additives which may optionally be added to the mixture with the carrier polymer, a so-called masterbatch.

[0234] The film of the present invention may be a multi-layer or a single-layer film, but is preferably a single-layer film.

[0235] According to the present invention, it is suitable that the single-layer film has a thickness of 5 to 300 μm, preferably 10 to 200 μm, more preferably 20 to 150 μm.

[0236] The blown film according to the present invention has a dart drop impact strength (DDI) measured on a 50 μm blown film according to ASTM D1709, method A of at least 60 g to 1700 g or more, preferably in the range of 80 g to 1700 g or more, and more preferably in the range of 100 g to 1700 g or more. The upper limit of 1700 g or more is due to the upper detection limit of 1700 g of the method.

[0237] The blown film according to the present invention also has a high Elmendorf tear strength as determined according to ISO 6383 / 2. When measured in the machine direction (MD), the tear strength is in the range of at least 5.0 N / mm to 50.0 N / mm, preferably in the range of 7.0 to 45.0 N / mm, and more preferably in the range of 7.5 to 40.0 N / mm.

[0238] The tear strength is in the range of at least 80.0 N / mm to 300.0 N / mm, preferably in the range of 90.0 to 250.0 N / mm, and more preferably in the range of 100.0 to 200.0 N / mm, measured in the transverse direction (TD).

[0239] The tensile modulus of the blown film itself should be moderate. Thus, the tensile modulus of a blown film based on a blend of components (A) and (B) should be less than 800 MPa, more preferably less than 750 MPa.

[0240] Thus, the tensile modulus measured according to ISO 527 at 23° C. on a blown film with a thickness of 50 μm is in the range of 200 to less than 800 MPa, preferably 250 to 750 MPa, more preferably 300 to 600 MPa in the longitudinal direction and in the transverse direction.

[0241] The films of the invention preferably have a seal initiation temperature (SIT) in the range of 80 to below 115°C, preferably 85 to 112°C, more preferably 87 to 108°C (determined on 50 μm blown films as described in the experimental part).

[0242] Furthermore, these films may also have a haze (measured according to ASTM D1003-00 on a 50 μm blown film) in the range of 0.5 to less than 5.0%, preferably 0.8 to less than 4.5%, more preferably 1.0 to less than 4.0% and a clarity (measured according to ASTM D1003-00 on a blown film having a thickness of 50 μm) of at least 80.0% to 100.0%, preferably at least 85.0% to 100.0%, more preferably at least 90.0% to 100.0%.

[0243] The blown films of the present invention have sufficient thermal stability to be sterilized.

[0244] The film can be sterilized by steam at a temperature range of about 120°C to 130°C for a duration of 15 to 45 minutes without destroying the good optical properties.

[0245] Therefore, the blown film according to the present invention has a haze value (determined according to ASTM D 1003-00 on a 50 μm blown film) after steam sterilization at 121° C. for 30 min in the range of 1.0 to less than 10.0%, preferably in the range of 1.2 to less than 8.0%, and more preferably in the range of 1.5 to less than 7.5%, and a clarity (determined according to ASTM D1003-00 on a blown film with a thickness of 50 μm) after sterilization (steam sterilization at 121° C. for 30 min) of at least 70.0%, preferably at least 75.0% and more preferably at least 80.0%, at most 100%.

[0246] From another perspective, there is a continuing need to provide films that show improvements in more than just one or two of these mechanical or optical properties. Therefore, it is desirable to provide products with well-balanced and continuously improving overall properties.

[0247] Such improvements in the overall performance of the blown film can be expressed in terms of optomechanical abilty.

[0248] In view of the present invention, optomechanical ability (OMA) is understood as the ratio of mechanical (especially tear strength (MD) and tensile (MD)) properties to optical properties (i.e. haze), wherein the mechanical properties aim to be as high as possible and the optical properties in terms of haze are desired to be as low as possible.

[0249] The optomechanical capability can be determined by multiplying the tensile modulus (MD) and the tear strength (MD) (Tear) and dividing this product by the haze measured on a 50 μm blown film (before sterilization).

[0250] Therefore, the optomechanical ability (OMA) is determined according to the formula given below:

[0251]

[0252] Therefore, in a further embodiment of the present invention, the optical mechanical ability (OMA) of the film measured on a 50 μm blown film is at least 900 [MPa*N / mm*%] to 4000 [MPa*N / mm*%], preferably in the range of 1000 [MPa*N / mm*%] to 3000 [MPa*N / mm*%].

[0253] It should be appreciated that any of the above parameters are measured according to the detailed tests given below. In any parameter for which narrower and broader embodiments are disclosed, these embodiments are disclosed in conjunction with the narrower and broader embodiments of the other parameters.

[0254] To produce a blown film, a melt of the blend of components (A) and (B) is extruded through an annular die and blown into a tubular film.

[0255] Thus, the present invention relates to a blown film of the present invention made by extruding a blend of components (A) and (B) as defined herein by conventional blown film extrusion, i.e. the blend of components (A) and (B) is extruded through a die, preferably an annular die, followed by formation of a bubble which collapses between rollers after solidification. The blown extrusion may preferably be carried out at a temperature in the range of 160 to 240° C., with cooling by water or preferably by blowing, typically air, at a temperature of 10 to 50° C. to provide a frost line height of 0.5 to 8 times the diameter of the die. The blow ratio should generally be in the range of 1.5 to 4, such as in the range of 2 to 4 and preferably in the range of 2.5 to 3.5.

[0256] Furthermore, the present invention relates to the use of the blown film according to the invention as packaging material, in particular as packaging material for foods and / or medical products.

[0257] Alternatively, the present invention also relates to the use of the blown film of the present invention as a sealing layer of a multilayer film.

[0258] Furthermore, the present invention also relates to an article comprising the blown film defined herein.

[0259] The invention will now be described with reference to the following non-limiting examples.

[0260] Experimental Section

[0261] A. Determination Method

[0262] Unless defined otherwise, the following definitions of terms and assay methods apply to the above general description of the invention as well as to the following examples.

[0263] Melt flow rate

[0264] Melt flow rate (MFR) is determined according to ISO 1133 - Determination of melt mass-flow rate (MFR) and melt volume-flow rate (MVR) of thermoplastics - Part 1: Standard method and is expressed in g / 10 min. The MFR indicates the flowability of a polymer and, therefore, its processability. The higher the melt flow rate, the lower the viscosity of the polymer. The MFR2 of polyethylene is determined at a temperature of 190°C and a load of 2.16 kg. The MFR2 of polypropylene is determined at a temperature of 230°C and a load of 2.16 kg.

[0265] Calculation of melt flow rate MFR2 (230°C) of polymer fraction (A-2):

[0266]

[0267] in

[0268] w(A1) is the weight fraction [in wt %] of polymer fraction A-1,

[0269] w(A2) is the weight fraction [in wt %] of polymer fraction A-2.

[0270] MFR(A1) is the melt flow rate MFR2 (230°C) of polymer fraction A-1 [in g / 10 min].

[0271] MFR(A) is the melt flow rate MFR2 (230°C) [in g / 10 min] of the C2C3 random copolymer (A).

[0272] MFR(A2) is the calculated melt flow rate MFR2 (230°C) [g / 10 min] of polymer fraction A-2.

[0273] Quantification of microstructure by NMR spectroscopy

[0274] Quantitative nuclear magnetic resonance (NMR) spectroscopy was further used to quantify the comonomer content and comonomer sequence distribution of the polymers. 1 H and 13 Quantitative measurements were recorded in solution on a Bruker Advance III400 NMR spectrometer operating at 400.15 and 100.62 MHz, respectively. 13 C{ 1 H} NMR spectroscopy. Nitrogen was used for all pneumatic devices, using 13 All spectra were recorded at 125°C with a C optimized 10 mm extended temperature probe. Approximately 200 mg of material was dissolved in 3 ml of 1,2-tetrachloroethane-d2 (TCE-d2) along with chromium (III) acetylacetonate (Cr(acac)3) to give a 65 mM solution of the relaxant in the solvent (Singh, G., Kothari, A., Gupta, V., Polymer Testing 28 5 (2009), 475). To ensure a homogeneous solution, the NMR tube was further heated in a rotary oven for at least 1 hour after the initial sample preparation in the heating block. After insertion into the magnet, the tube was rotated at 10 Hz. This setup was chosen primarily to obtain high resolution and is quantitatively required for accurate quantification of ethylene content. Standard single pulse excitation without NOE was used, using an optimized tip angle, a 1 s recycle delay, and a two-stage WALTZ16 decoupling scheme (Zhou, Z., Kuemmerle, R., Qiu, X., Redwine, D., Cong, R., Taha, A., Baugh, D. Winniford, B., J. Mag. Reson. 187 (2007) 225; Busico, V., Carbonniere, P., Cipullo, R., Pellecchia, R., Severn, J., Talarico, G., Macromol. Rapid Commun. 2007, 28, 1128). A total of 6144 (6k) transient values ​​were obtained for each spectrum.

[0275] A proprietary computer program was used to quantify 13 C{ 1H} NMR spectra are processed, integrated and relevant quantitative properties are determined from the integration. All chemical shifts are indirectly referenced to the central methylene group of the ethylene block (EEE) at 30.00 ppm using the chemical shift of the solvent. This method allows for comparable references even if this structural unit is not present. Characteristic signals corresponding to ethylene incorporation have been observed (Cheng, HN, Macromolecules 17 (1984), 1950).

[0276] In cases where characteristic signals corresponding to 2,1 erythro-type regio defects are observed (as described in L. Resconi, L. Cavallo, A. Fait, F. Piemontesi, Chem. Rev. 2000, 100(4), 1253, Cheng, HN, Macromolecules 1984, 17, 1950 and WJ. Wang and S. Zhu, Macromolecules 2000, 33 1157), it is necessary to correct for the influence of the regio defects on the determined properties. Characteristic signals corresponding to other types of regio defects are not observed.

[0277] The method of Wang et al. (Wang, WJ., Zhu, S., Macromolecules 33 (2000), 1157) was used to 13 C{ 1 The comonomer fraction is quantified by integrating multiple signals over the entire spectral region of the {H} spectrum. This method was chosen due to its robustness and ability to account for the presence of regio defects when required. The integration region was slightly adjusted to improve applicability over the entire range of comonomer contents encountered.

[0278] For systems where only isolated ethylene in the PPEPP sequence was observed, the method of Wang et al. was modified to reduce the effect of non-zero integrals at sites known to be absent. This approach reduced the overestimation of the ethylene content for such systems and was achieved by reducing the number of sites used to determine the absolute ethylene content to:

[0279] E=0.5(Sββ+Sβγ+Sβδ+0.5(Sαβ+Sαγ))

[0280] Using this set of sites, the corresponding integral equation becomes:

[0281] E=0.5(I H +I G +0.5(I C +I D ))

[0282] The same symbols are used as in the article by Wang et al. (Wang, WJ., Zhu, S., Macromolecules 33 (2000), 1157). No modifications were made to the equations for absolute propylene content.

[0283] Calculate the mole percentage of comonomer incorporation from the mole fraction:

[0284] E[mol%]=100*fE

[0285] Calculate the weight percent of comonomer incorporation from the mole fraction:

[0286] E[weight%]=100*(fE*28.06) / ((fE*28.06)+((1-fE)*42.08))

[0287] The triad level comonomer sequence distribution was determined using the analytical method of Kakugo et al. (Kakugo, M., Naito, Y., Mizunuma, K., Miyatake, T. Macromolecules 15 (1982) 1150). This method was chosen due to its robustness, and the integration region was slightly adjusted to improve applicability to a wider range of comonomer content.

[0288] Calculation of the comonomer content of the second polymer fraction (A-2):

[0289]

[0290] in

[0291] w(A-1) is the weight fraction [in wt %] of the first polymer fraction (A-1),

[0292] w(A-2) is the weight fraction [in wt %] of the second polymer fraction (A-2),

[0293] C(A-1) is the comonomer content [in % by weight] of the first polymer fraction (A-1),

[0294] C(A) is the comonomer content of the C2C3 random copolymer (A) [in % by weight],

[0295] C(A-2) is the calculated comonomer content [in wt. %] of the second polymer fraction (A-2).

[0296] Xylene Cold Solubles (XCS)

[0297] The xylene solubles (XS) fraction, as defined and described in the present invention, is determined according to ISO 16152 as follows: 2.0 g of polymer is dissolved in 250 ml of p-xylene under stirring at 135° C. After 30 minutes, the solution is allowed to cool for 15 minutes at ambient temperature and then allowed to stand for 30 minutes at 25+ / -0.5° C. The solution is filtered into two 100 ml flasks with filter paper. The solution from the first 100 ml container is evaporated in a stream of nitrogen and the residue is dried under vacuum at 90° C. until constant weight is reached. The xylene soluble fraction (percentage) can then be determined as follows:

[0298] XS% = (100*m*V0) / (m0*v); m0 = initial polymer amount (g); m = residue weight (g); V0 = initial volume (ml); v = volume of analyzed sample (ml).

[0299] Melting temperature T m and crystallization temperature T c

[0300] Parameter determinations were performed on 5 to 7 mg samples using a TA Instrument Q2000 Differential Scanning Calorimetry (DSC). The DSC was run according to ISO 11357 / Part 3 / Method C2 in a heating / cooling / heating cycle over a temperature range of -30°C to +225°C at a scanning rate of 10°C / min. The crystallization temperature (T c ) is determined by the cooling step, while the melting temperature (T m ) is determined from the second heating step. The melting temperature and crystallization temperature are taken from the peaks of the endotherm and the exotherm.

[0301] Sealing Initiation Temperature (SIT); (Sealing End Temperature (SET), Sealing Range)

[0302] This method determines the sealing temperature range (sealing range) of polypropylene films, in particular blown films. The sealing temperature range is the temperature range in which the film can be sealed according to the conditions given below. The lower limit (heat seal initiation temperature (SIT)) is the sealing temperature at which a seal strength of 5 + / - 0.5 N is obtained. The upper limit (sealing end temperature (SET)) is reached when the film sticks to the sealing device.

[0303] The sealing range is measured on a J&B Universal Sealing Machine Type 3000 on a multilayer film as described below using the following parameters:

[0304] Sample width: 25.4mm

[0305] Sealing pressure: 0.1N / mm 2

[0306] Sealing time: 0.1s

[0307] Cooling time: 99s

[0308] Peeling speed: 10mm / s

[0309] Starting temperature: 80℃

[0310] End temperature: 150℃

[0311] Increment: 10℃

[0312] At each seal bar temperature, the specimens were sealed from A to A, and the seal strength (force) was measured at each step. The temperature at which the seal strength reached 5N was measured.

[0313] Flexural modulus

[0314] Flexural modulus according to ISO 178 at 23°C for 80×10×4 mm injection molded according to EN ISO 1873-2 3 Measured on a test bar in 3-point bending.

[0315] Tear strength (determined as Elmendorf Tear (N)): Applicable for both the machine direction (MD) and the transverse direction (TD) measurements. Tear strength is measured using the ISO 6383 / 2 method. The force required to propagate a tear on a film sample is measured using a pendulum apparatus. The pendulum swings through an arc under the force of gravity, tearing the specimen from the pre-cut slit. One side of the film sample is fixed by the pendulum and the other side is fixed by a fixing clamp. The tear strength is the force required to tear the specimen. The relative tear strength (N / mm) is then calculated by dividing the tear strength by the film thickness.

[0316] Tensile modulus

[0317] The tensile modulus in the longitudinal and transverse directions was determined according to ISO 527-3 at 23° C. on films produced as shown below. The test was carried out at a crosshead speed of 1 mm / min.

[0318] Drop Dart Impact Strength (DDI)

[0319] Dart impact is measured using ASTM D1709, Method A (alternative test technique) from films produced as shown below. A dart with a 38 mm diameter hemispherical head is dropped from a height of 0.66 m onto the film clamped over the hole. Groups of 20 specimens are tested consecutively. One weight is used for each group, and the weight is increased (or decreased) from group to group in uniform increments. The weight that causes 50% of the specimens to fail is calculated and reported.

[0320] Haze and clarity

[0321] Haze and clarity were measured according to ASTM D 1003-00 on films produced as shown below.

[0322] Steam sterilization was performed in a Systec D series machine (Systec Corporation, USA). The samples were heated starting from 23° C. at a heating rate of 5° C. / min. After 30 min at 121° C., they were immediately removed from the steam sterilizer and stored at room temperature until further processing.

[0323] B. Examples

[0324] C2C3 random copolymer (component A)

[0325] The catalyst used in the polymerization process for the C2C3 random copolymers of Examples (IE1, IE2) and (CE1) of the present invention was prepared as follows:

[0326] Metallocene (MC1) (rac-trans-dimethylsilanediyl(2-methyl-4-phenyl-5-methoxy-6-tert-butyl-indenyl)(2-methyl-4-(4-tert-butylphenyl)indenyl)zirconium dichloride) has been synthesized according to the procedure described in WO2013007650, E2.

[0327]

[0328] Preparation of MAO-silica carrier

[0329] A steel reactor equipped with a mechanical stirrer and a filter screen was flushed with nitrogen and the reactor temperature was set to 20°C. Then, AGC Si-Tech's silica grade DM-L-303 (7.4 kg) pre-calcined at 600°C was added from the feed bucket, and then carefully pressurized and depressurized with nitrogen using a manual valve. Toluene (32 kg) was then added. The mixture was stirred for 15 minutes. Then, a 30% by weight solution of MAO from Lanxess in toluene (17.5 kg) was added through the feed line at the top of the reactor within 70 minutes. The reaction mixture was then heated to 90°C and stirred for another two hours at 90°C. The slurry was allowed to settle and the mother liquor was filtered off. At 90°C, the MAO-treated support was washed twice with toluene (32 kg), followed by settling and filtering. The reactor was cooled to 60°C and the solid was washed with heptane (32.2 kg). Finally, the MAO treated SiO2 was dried at 60°C under a nitrogen stream for 2 hours and then dried under vacuum (-0.5 bar, gauge) with stirring for 5 hours. The MAO treated support was collected as a free flowing white powder and was found to contain 12.6% aluminum (by weight).

[0330] Catalyst system preparation

[0331] At 20°C, 30 wt% MAO in toluene (2.2 kg) was added to a steel reactor under nitrogen protection by a burette. Toluene (7 kg) was then added under stirring. Metallocene MC1 (286 g) was added from a metal cylinder and then rinsed with 1 kg toluene. The mixture was stirred for 60 minutes at 20°C. Trityl tetrakis (pentafluorophenyl) borate (336 g) was then added from a metal cylinder and subsequently rinsed with 1 kg toluene. The mixture was stirred at room temperature for 1 h. The resulting solution was added to the stirred cake of the MAO-silica support prepared as described above for more than 1 hour. The cake was placed for 12 hours, then dried for 2 hours at 60°C under a N2 flow, and dried for another 5 hours under vacuum (-0.5 bar, gauge pressure) under stirring. The dried catalyst was sampled in the form of a pink free-flowing powder containing 13.9 wt% Al and 0.26 wt% Zr.

[0332] The polymerization for preparing the C2C3 random copolymer (PRC) of the present invention was carried out in a Borstar pilot plant with a 2-reactor arrangement (loop-gas phase reactor (GPR1)). The polymerization conditions are given in Table 1.

[0333] Table 1:

[0334] Component (A) Prepolymerization reactor Temperature [℃] 25 Pressure [Pa] 5149 Catalyst feed [g / h] 2.0 <![CDATA[C3 feed [kg / h]]]> 52 <![CDATA[H2 feed [g / h]]]> 0.3 Residence time [h] 0.4 Loop reactor Temperature [℃] 68 Pressure [Pa] 5385 <![CDATA[Feed H2 / C3 ratio [mol / kmol]]]> 0.24 <![CDATA[Feed C2 / C3 ratio [mol / kmol]]]> 48.3 Polymer split ratio (split) [weight %] 67 <![CDATA[MFR2[g / 10min] (MFR of A-1)]]> 2.0 Total C2 rings [wt%] (C2 of A-1) 3.7 XCS ring tube [weight %] 3.5 Residence time (h) 0.4 GPR1 Temperature [℃] 75 Pressure [Pa] 2500 <![CDATA[H2 / C3 ratio [mol / kmol]]]> 2.0 <![CDATA[C2 / C3 ratio [mol / kmol]]]> 224 Polymer residence time (h) 1.8 Polymer split ratio [wt%] 33 <![CDATA[Total MFR2 [g / 10 min]]]> 1.1 <![CDATA[MFR2 in GPR1 [g / 10 min] (MFR of A-2)]]> 0.3 <![CDATA[Total C2 [wt%] (loop reactor + GPR1)]]> 4.1 <![CDATA[C2 [wt%] in GPR1 (C2 of A-2)]]> 4.9 XCS [wt%] 4.7

[0335] The polymer powder was compounded at 220° C. in a co-rotating twin-screw extruder Coperion ZSK 57 with 0.2% by weight of an anti-caking agent (synthetic silica; CAS No. 7631-86-9); 0.1% by weight of an antioxidant (Irgafos 168FF); 0.1% by weight of a sterically hindered phenol (Irganox 1010FF); 0.02% by weight of calcium stearate and 0.02% by weight of a non-lubricating stearate (synthetic hydrotalcite; CAS No. 11097-59-9).

[0336] Table 2: Polymer properties

[0337] Granules Component (A) XCS [wt%] 4.7 <![CDATA[Total C2 [wt%]]]> 4.1 <![CDATA[MFR2[g / 10min]]]> 1.1 Tm[℃] 125 Tc[℃] 85

[0338] For Inventive Examples IE1 and IE2, the C2C3 random copolymer (A) produced as described above was mixed with the ethylene-based plastomer (B).

[0339] The following commercially available plastomers (B) have been used:

[0340] Queo TM 8201, ethylene-octene plastomer, density 882kg / m 3, MFR2 (190°C, 2.16 kg) of 1.1 g / 10 min and a melting point of 76°C, is commercially available from Borealis AG.

[0341] The mixing was carried out in a co-rotating twin-screw extruder Coperion ZSK 57.

[0342] Membrane production

[0343] All film properties are measured on 50 μm thick monolayer blown films produced on a Collin blown film line. The line has a screw diameter of 30 millimeters (mm), an L / D of 30, a die diameter of 60 mm, a die gap of 1.5 mm, and a duo-lip cooling ring. The film samples were produced at 190° C. with an average thickness of 50 μm, a blow-up ratio of 2.5, and an output of approximately 8 kilograms per hour (kg / h). The properties of the films can be seen in Table 3.

[0344] Table 3:

[0345] CE1 IE1 IE2 <![CDATA[C2C3 copolymer]]> weight% 100 90 75 Queo 8201 weight% 10 25 50μm BF Tensile modulus MD MPa 638 527 341 Tensile modulus TD MPa 664 540 319 DDI g 43 116 >1700 Haze / bs % 4.9 3.9 2.6 Clarity / bs % 91.8 91.8 90.7 Haze / as % 4.9 4.6 5.2 Clarity / as % 91.1 89.9 85.0 Tear / MD N / mm 6.6 7.6 19.7 Tear / TD N / mm 21.2 119.4 168.0 SIT ℃ 109 105 90 OMA 859 1027 2584

[0346] Before bs steam sterilization

[0347] After steam sterilization

[0348] As can be clearly seen from the above table, the blown film of the present invention shows a favorable combination of low seal initiation temperature (SIT), high tear resistance and impact strength, and good optical properties (such as low haze) based on a specific blend. In addition, this film has improved overall properties, i.e. high OMA.

Claims

1. A blown film comprising at least 95.0% by weight of a blend of components A and B, the blend comprising A: 60.0 wt% to 95.0 wt% of a C2C3 random copolymer, the C2C3 random copolymer consisting of, 45.0 to 85.0 wt. % of polymer fraction A-1, said polymer fraction A-1 having (i) an ethylene content in the range of 1.5 to 5.0 wt.%, and (ii) a melt flow rate MFR2 measured according to ISO 1133 at a temperature of 230° C. under a load of 2.16 kg in the range of 0.8 to 8.0 g / 10 min, and 15.0 to 55.0 wt. % of polymer fraction A-2, said polymer fraction A-2 having (i) an ethylene content in the range of 4.0 to 10.0 wt.%, and (ii) a melt flow rate MFR2 measured according to ISO 1133 at a temperature of 230° C. under a load of 2.16 kg in the range of 0.1 to 3.0 g / 10 min, wherein the ethylene content of the polymer fraction A-2 is higher than the ethylene content of the polymer fraction A-1, and the melt flow rate MFR2 of the polymer fraction A-2 measured at a temperature of 230°C and under a load of 2.16 kg according to ISO 1133 is lower than the MFR2 of the polymer fraction A-1 measured at a temperature of 230°C and under a load of 2.16 kg according to ISO 1133, and wherein the C2C3 random copolymer has (a) a total ethylene content in the range of 1.0 to 7.0 weight percent; (b) a melt flow rate MFR2 measured according to ISO 1133 at a temperature of 230° C. under a load of 2.16 kg in the range of 0.5 to 4.0 g / 10 min; and (c) a melting temperature Tm determined by DSC according to ISO 11357 of 110° C. to 140° C., The C2C3 random copolymer is prepared using a single active site catalyst. B: 5.0 wt% to 40.0 wt% of a vinyl plastomer having (i)860kg / m 3 Up to 900kg / m 3 The density according to ISO 1183, and (ii) an MFR2 measured according to ISO 1133 at a temperature of 190° C. under a load of 2.16 kg in the range of 0.1 to 50.0 g / 10 min, (iii) a comonomer selected from C4 to C8 α-olefins, The blown film has a) a dart drop impact strength (DDI) of at least 60 g as measured on a 50 μm blown film according to ASTM D1709, Method A, and b) Elmendorf tear strength determined according to ISO 6383-2 measured in the machine direction (MD) in the range of 5.0 N / mm to 50.0 N / mm and in the transverse direction (TD) in the range of 80.0 N / mm to 300.0 N / mm.

2. The blown film according to claim 1, wherein the C2C3 random copolymer has a xylene cold soluble (XCS) fraction measured at 25°C according to ISO 16152 of from 0.6 to 12.0 wt.%.

3. The blown film according to claim 1 or 2, wherein the C2C3 random copolymer has (a) a total ethylene content in the range of 1.5 to 6.5 wt. %, (b) a melt flow rate MFR2 measured according to ISO 1133 at a temperature of 230° C. under a load of 2.16 kg in the range of 0.7 to 3.5 g / 10 min, and (c) a melting temperature Tm determined by DSC according to ISO 11357 of 115°C to 135°C.

4. The blown film of claim 1 or 2, wherein the vinyl plastomer has (i)865kg / m 3 Up to 895kg / m 3 Density according to ISO 1183, (ii) an MFR2 measured according to ISO 1133 at a temperature of 190°C under a load of 2.16 kg in the range of 0.3 to 20.0 g / 10 min, and (iii) a comonomer selected from 1-butene or 1-octene.

5. The blown film of claim 1 or 2, wherein the blown film comprises at least 95.0 wt% of a blend comprising 65.0 to 93.0 wt% of the C2C3 random copolymer and 7.0 to 35.0 wt% of the ethylene-based plastomer.

6. The blown film of claim 1 or 2, wherein the blown film comprises at least 98.0 wt% of the blend of component A and component B.

7. The blown film according to claim 1 or 2, wherein the blown film has a dart drop impact strength (DDI) measured according to ASTM D1709, method A on a 50 μm blown film in the range of at least 80 g.

8. The blown film according to claim 1 or 2, wherein the blown film has an Elmendorf tear strength measured in the machine direction (MD) in the range of 7.0 to 45.0 N / mm and in the transverse direction (TD) in the range of 90.0 to 250.0 N / mm, determined according to ISO 6383-2.

9. The blown film according to claim 1 or 2, wherein the blown film has a tensile modulus in the longitudinal direction and in the transverse direction, measured at 23°C according to ISO 527 on a blown film having a thickness of 50 μm, of 200 to 800 MPa.

10. The blown film according to claim 1 or 2, wherein the blown film has The haze measured according to ASTM D1003-00 on a blown film having a thickness of 50 μm is between 0.5 and 5.0%, and 80.0% to 100.0% clarity measured according to ASTM D1003-00 on a blown film having a thickness of 50 μm.

11. The blown film according to claim 1 or 2, wherein the blown film has a haze value measured according to ASTM D 1003-00 on a 50 μm blown film after steam sterilization at 121° C. for 30 min in the range of 1.0 to 10.0%, and a clarity measured according to ASTM D1003-00 on a blown film having a thickness of 50 μm after steam sterilization at 121° C. for 30 min of at least 70.0%.

12. The blown film according to claim 1 or 2, wherein the blown film has an optical mechanical ability (OMA) of 900 MPa*N / mm*% to 4000 MPa*N / mm*% measured on a 50 μm blown film according to the following formula: Wherein the tensile modulus [MPa] denotes the tensile modulus in the longitudinal direction on a blown film having a thickness of 50 μm measured at 23° C. according to ISO 527, in units of MPa, Tear [N / mm] represents the Elmendorf tear strength measured in the longitudinal direction in N / mm according to ISO 6383-2. The haze [%] indicates the haze measured on a blown film having a thickness of 50 μm in accordance with ASTM D1003-00, in units of %.

13. The blown film according to claim 1 or 2, wherein the blown film is a monolayer film.

14. Use of the blown film according to any one of claims 1 to 13 as a sealing layer in a multilayer film or as a packaging material.

Citation Information

Patent Citations

  • Polypropylene films with improved optics and mechanical properties

    EP3031849A1

  • Composition based on pp random copolymers and elastomers

    EP3280768A1

  • Multi-stage process for producing polyethylene

    WO1992012182A1

  • A process for forming a carrier material

    WO1994014856A1

  • Supported olefin polymerization catalyst, its preparation and use

    WO1995012622A1